Increase in the number of intrafusal muscle fibres in rat muscles after neonatal motor denervation - Zelená, J; Soukup, T (Neuroscience, 1993)
Rat muscle spindles disintegrate after total neonatal muscle denervation in which both sensory and motor axons are cut, but develop almost normally during the first three weeks after neonatal de-efferentation, attaining the usual complement of four intrafusal fibres, two bag and two chain fibres. Thereafter additional intrafusal fibres differentiate in most of the de-efferented spindles. We have examined the development of supernumerary fibres in muscle spindles of the rat hind limb muscles one to four months after neonatal de-efferentation using transmission electron microscopy. Additional intrafusal fibres originate both from activated intrafusal myosatellites and by different forms of fibre division. In a sample of 27 muscle spindles examined along the A zone five weeks after de-efferentation, the mean number of intrafusal fibre profiles increased almost two-fold to 7.9 +/- 3.3 (S.D.). Up to 20 intrafusal fibre profiles per spindle cross-section were found in muscles de-efferented for four months. The supernumerary fibres were apparently derived from all three intrafusal fibre types, but predominantly from the chain fibres. It is noteworthy that de-efferentation which causes wasting of extrafusal muscle initiates myogenesis and maintains additional intrafusal fibres within the spindle capsules.
Keywords: Microscopy, Electron; Rats; motorické neurony; Animals, Newborn; Motor Neurons; neurony aferentní; Muscle Denervation; elektronová mikroskopie; Rats, Wistar; novorozená zvířata; Muscles; krysa rodu Rattus; denervace svalu; Neurons, Afferent; zvířata; svaly; nervová vlákna; potkani Wistar; Nerve Fibers; Animals